Primary signet-ring stromal tumor of the testis - Michal, Michal; Hes, Ondřej; Kazakov, Dimitar (Virchows Archiv, 2005)
We present, in a 47-year-old man, the first case of the signet-ring stromal tumor of the testis. The tumor was located beneath the tunica albuginea surrounded by the testicular tubules and rete testis. It was sharply circumscribed by a thin and irregular fibrous capsule. Histologically, it was composed of cells with a widespread signet-ring cell change separated by fibrous stroma. In some places, the signet-ring cells formed vague Indian files, thus resembling metastatic carcinomas with signet-ring cell morphology. Under high magnification, most of the cytoplasm of the tumor cells was seen to be replaced by an empty clear vacuole which pushed the nuclei to the periphery of the cells. Some of the nuclei were indented by the cytoplasmic vacuoles, others were without indentation. Only in a small area did the tumor show cells without a signet-ring cell change. They looked like epithelioid fibroblasts forming abortive and vaguely tubular structures. Mitoses and necroses were absent. Mucicarmine and PAS stains were negative. Immunohistochemically, the tumor was vimentin positive and it was negative with antibodies to cytokeratins, inhibin, prostatic acid phosphatase, prostate-specific antigen, smooth muscle actin, S-100 protein, EMA and calretinin. The signet-ring stromal tumor of the testis is thus similar morphologically and immunohistochemically to the signet-ring stromal tumor of the ovary. The patient was free of recurrence and metastasis 3 years after the excision.
Keywords: Humans; lidé středního věku; Biomarkers, Tumor; Immunoenzyme Techniques; výsledek terapie; testikulární nádory; lidé; Vimentin; Stromal Cells; přežití bez známek nemoci; buňky stromatu; Carcinoma, Signet Ring Cell; nádorové biomarkery; imunoenzymatické techniky; Testicular Neoplasms; karcinom z prstenčitých buněk; Male; Middle Aged; Treatment Outcome; Disease-Free Survival; mužské pohlaví; vimentin